National forage survey results: trace mineral and related nutrient levels - L. Corah; D. Dargatz; C. Peters (Kansas Agricultural Experiment Station Research Reports, 1996)
A National Forage Survey was conducted in 18 states to determine the trace mineral and related nutrient content of forages grown in the United States. Most forages sampled were harvested hays utilized as winter feed for beef cow herds. The trace element most commonly deficient in the forages sampled was zinc. Copper and cobalt levels were adequate in 36 and 34.1% of the samples, respectively. In contrast, manganese was adequate (above 40 ppm) in 76% of the samples and was deficient (below 20 ppm) only in 4.7%. The copper antagonists, such as iron and molybdenum, were marginal to high in 28.7% and 57.8% of the samples, respectively, indicating that both of these elements are often present in levels that can cause a reduction in copper availability. Of the 352 samples collected in 18 states, the trace mineral most likely to be deficient was zinc, followed by selenium and cobalt.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Trace minerals; Forage survey; Forages